Penerapan Finite-State Machines untuk Peningkatan Performa Frame Per Second dalam Game Multiplayer Real Time Strategy - Nicholas Sutikno; Djoni Haryadi Setiabudi; Alvin Nathaniel Tjondrowiguno (Jurnal Infra, 2019)
Games are in great demand from children to adults and games can also be played from several available platforms such as PC, mobile and console. Games have various genres such as Action, Adventure, RPG, Strategy, and many other types of genres for games. The purpose of this paper is to apply Finite-State Machines to improve FPS performance in games so that the game becomes light and comfortable to play. In previous studies FSM was used for testing AI algorithms and to assist in story formation introduce history in the game. Finite-State Machines are a method or design that will be created and implemented so that AI can make its own decisions based on predetermined conditions. Using the Finite-State Machines method because only one task is actively read so that other tasks are not read by AI in the program and light computing.The game genre that will be implemented in the game is the Real Time Strategy entitled "Attack on Toys". In the game there was a decrease in FPS performance because of the many soldiers in the game. Because this was implemented by FSM to improve the performance of the Game and the Game must still be fun when played by the player. FPS performance testing by comparing games without using FSM, using the first FSM design, and using a second design. Questionnaire testing was also conducted to find out whether the game was fun and whether the AI could work well when the game was played.Test results after the implementation of Finite-State Machines that from the results of comparison testing can increase FPS performance by up to 90%. Based on the results of the Game questionnaire it is still fun to play and AI continues to work as expected when played by players after the implementation of Finite-State Machines without reducing the quality of the game itself.